If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2x = 7 + -1x Solving 6 + 2x = 7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 6 + 2x + x = 7 + -1x + x Combine like terms: 2x + x = 3x 6 + 3x = 7 + -1x + x Combine like terms: -1x + x = 0 6 + 3x = 7 + 0 6 + 3x = 7 Add '-6' to each side of the equation. 6 + -6 + 3x = 7 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 7 + -6 3x = 7 + -6 Combine like terms: 7 + -6 = 1 3x = 1 Divide each side by '3'. x = 0.3333333333 Simplifying x = 0.3333333333
| 2x^3-8x^2-64x-55296=0 | | -180=-4(6n+3) | | 20-7b=-66+21 | | 3x^2-9x=-5x-5 | | 3n+4.5-n=10.5 | | 14(14y+10)= | | 4(2x-3)-7(x-2)= | | (-2.9)8x-1=(-2.9)9x+4 | | 5z-8=33 | | x-24=-36 | | -7(6-4b)=98 | | h(x)=X^4-2x^3+14x^2+6x-51 | | (6x-3)+7=44 | | 9(21-1x)=17(2x+1) | | 3z+11+28z=50+29z-(-1) | | 4y-19y=60 | | -(4x+3)-(-3x-5)=3 | | 5x-4=5(2x-3) | | 10x-1(3x-2)=30 | | 2(x-3)=3y | | -5(4y-5)+20y= | | -4+3n=4(n+2) | | 4(5t+1)-8=t-(t-3) | | -5(2p+4)-22=3(3p+5) | | X^2+X-0.003=0 | | -2.5+8.9=2.5 | | -2.5+8.9=2.5 | | (-33)=(-17)-n | | (-33)=(-17)-n | | 21+21j+j+19j=125+2j | | -11m+3m=12-44 | | 2p^2+15p+13=0 |